Upper and lower $s$-$(τ_1,τ_2)p$-continuous multifunctions (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower $s$-$(τ_1,τ_2)p$-continuous multifunctions. Furthermore, several characterizations of upper and lower $s$-$(τ_1,τ_2)p$-continuous multifunctions are investigated.
Keywords: $(τ_1,τ_2)p$-open set; upper $s$-$(τ_1,τ_2)p$-continuous multifunction; lower $s$-$(τ_1,τ_2)p$-continuous multifunction